The event of music history - Harper-Scott, J. P. E. (John Paul Edward), 1977- (The Boydell Press, 2021)
This book presents a new theory of how to write music history, and offers an exemplar of this new theory in action, in a series of four chapter-length reflexions on Beethoven's heroic style. The first book-length theory of music history since Carl Dahlhaus's Foundations of Music History, it brings musicology to the cutting edge of debates in the postmodern philosophy of history. While the book engages with current thinking, it also goesfurther than the postmodern critique of history writing to find a new and positive basis for the writing of music history. In so doing the book revisits the philosophy of Alain Badiou: in place of a focus on the facts, the objects of history, whose problematic relation to history writing the theorists have demonstrated, the book proposes a focus instead on the subjects of history, the'faithful', 'reactive, and'obscure'responses to an'Event'(a kind of rapture of ontology which brings the actors involved closer to a truth). It sees musical materials (the styles, techniques, and musical'language'handed down to composers by history) in a dialectical relationship with the human beings who are music's manifold historical actors.